American Dream As Utopian Fantasy: A Study Of Ray Bradbury’s Something Wicked This Way Comes - S. Rupapriya; Dr. J. Arul Anand (Revista Electronica de Veterinaria, 2024)
The history of American Dream glorifies an endless opportunities to the people of America which includes rights, liberty, being successful and equality that have to be possessed through hard work and dedication.  This can create a better or ideal society, which can also be termed as Utopia.  Through Ray Bradbury’s Something Wicked This Way Comes this American Dream turns into a mere fantasy.  The carnival owned by Mr. Dark and Cooger prevails the townspeople and satisfies their wish which is a trap to get them into the pit, from where people looses their own nature and their loved ones particularly for whom they wanted to change themselves.  Anyhow Will and his father Charles Halloway save the townspeople and Jim, Will’s best friend by defeating the Sinister Carnival.  This articles aims to explore the American Dream as Utopian Fantasy where at last through the character of Charles Halloway who ignores the fact that he is old and accept to be old rather changing into youth,  he works hard and dedicates himself to save his son Will and the townspeople.  Here the article also provides a great vision that American Dream is alive when the people accepts and fulfilled with their own properties.